A lithium ion battery separator suitable for cold pressing and a method of making the same

CN120691042BActive Publication Date: 2026-10-20JIANGSU HORIZON NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510935447.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-08
Publication Date
2026-10-20
Estimated Expiration
2045-07-08

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种适用于冷压的锂离子电池隔膜及其制备方法,以解决现有技术中提出的的问题

Benefits of technology

与现有技术相比,本发明的有益效果是:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of lithium ion battery separators suitable for cold pressing and preparation method thereof, it is related to lithium ion battery technical field.The separator of the application includes base film and coating layer, coating layer is composed of polyvinylidene fluoride, polyacrylonitrile adhesive, aliphatic amide dispersant, polyvinyl alcohol, acrylic monomer, emulsifier and initiator etc.;Preparation method includes polyvinyl alcohol modified acrylic emulsion preparation, coating layer slurry preparation, coating separator preparation and other steps.The lithium ion battery separator developed in the application not only has excellent adhesive property, puncture strength, but also can reduce battery end energy consumption and improve production efficiency, suitable for cold pressing process, solve the problem of low efficiency, high energy consumption of traditional hot pressing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, specifically to a lithium-ion battery separator suitable for cold pressing and its preparation method. Background Technology

[0002] The battery separator is an important component of lithium-ion batteries. Structurally, it directly separates the positive and negative electrodes to prevent short circuits, while also allowing ions to migrate between the positive and negative electrodes. The performance of the separator directly determines the battery's interface performance, cycle performance, and safety performance.

[0003] Currently, traditional separators composed of polyolefin-based membranes and ceramic coatings are no longer able to meet the ever-upgrading demands of battery technology. While functional coatings that have emerged in the market can improve separator performance to some extent, adhesive coatings with polyvinylidene fluoride as the main component have obvious limitations: their adhesive strength needs to be enhanced, and they require hot pressing to achieve adhesion to the electrode sheets.

[0004] As lithium-ion batteries move towards larger sizes, cell thickness continues to increase, and the hot pressing process has revealed a series of drawbacks: the upper and lower heating plates cannot effectively transfer heat to the center of the cell thickness, which not only leads to a significant increase in hot pressing time and a significant reduction in production efficiency, but also fails to guarantee the uniformity of the hot pressing interface, and increases the energy consumption of the production line.

[0005] Therefore, developing a lithium-ion battery separator suitable for cold pressing technology has become an important research direction in this field. Summary of the Invention

[0006] The purpose of this invention is to provide a lithium-ion battery separator suitable for cold pressing and a method for preparing the same, so as to solve the problems raised in the prior art.

[0007] To achieve the above objectives, the present invention provides the following technical solution: A lithium-ion battery separator suitable for cold pressing includes a base film and a coating layer disposed on the surface of the base film.

[0008] Furthermore, the base membrane is a polyolefin separator.

[0009] Furthermore, the components used in preparing the coating layer include: polyvinylidene fluoride, adhesive, dispersant, polyvinyl alcohol, acrylic monomers, emulsifier, and initiator.

[0010] Furthermore, the polyvinylidene fluoride is a PVDF-HFP powder with a grafting rate of 2%-8%, a molecular weight of 500,000-1,000,000, and a particle size of 4-9µm.

[0011] Furthermore, the membrane thickness is 5-20µm.

[0012] Furthermore, the adhesive is a polyacrylonitrile polymer, and the dispersant is an aliphatic amide dispersant.

[0013] Furthermore, the acrylic monomer is one or more of acrylic acid, methyl acrylate, ethyl acrylate, and methyl methacrylate; The emulsifier is one or a mixture of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, fatty alcohol polyoxyethylene ether, and sodium allyl hydroxypropyl sulfonate. The initiator is one or a mixture of ammonium persulfate, potassium persulfate, and sodium persulfate.

[0014] A method for preparing a lithium-ion battery separator suitable for cold pressing includes the following steps: S1: Preparation of polyvinyl alcohol modified acrylic emulsion: Acrylic monomers, emulsifiers, and deionized water are mixed and stirred to prepare a pre-emulsion; a polyvinyl alcohol solution is heated to 70-80℃, and the pre-emulsion and initiator solution are added dropwise, and the reaction is maintained at this temperature for 1-2 hours to obtain a polyvinyl alcohol modified acrylic emulsion. S2: Preparation of coating slurry: Dispersant, binder and ultrapure water are stirred to form a dispersion; polyvinylidene fluoride and polyvinyl alcohol modified acrylic emulsion are added in sequence and stirred to obtain coating slurry; S3: Preparation of coated diaphragm: The coating slurry is applied to the surface of the base membrane and dried to form a coating layer, thus obtaining a coated diaphragm.

[0015] Furthermore, S1 includes the following steps: Mix acrylic monomers, emulsifiers and deionized water, and stir at 200-500 r / min for 30-60 min to pre-emulsify and prepare a pre-emulsion. Polyvinyl alcohol is added to deionized water, heated to 80-95℃ and stirred to dissolve. After complete dissolution, it is cooled to room temperature to obtain a polyvinyl alcohol solution. Take the initiator, add deionized water to dissolve it, and obtain the initiator solution; The polyvinyl alcohol solution is heated to 70-80℃, and the pre-emulsion and initiator solution are added dropwise. The mixture is stirred at a speed of 500-600 r / min and kept at this temperature for 1-2 hours. After cooling to room temperature, a polyvinyl alcohol modified acrylic emulsion is obtained.

[0016] Furthermore, S2 includes the following steps: Mix the dispersant, binder and ultrapure water, and stir at 20-40 r / min for 10-30 min to prepare a dispersion. Add polyvinylidene fluoride and stir to form a solution; add polyvinyl alcohol modified acrylic emulsion and stir at 20-40 r / min for 10-30 min to obtain the coating slurry.

[0017] Furthermore, S3 includes the following steps: The coating slurry is applied to the surface of the base film by spraying or roller coating, and dried at 40-80℃ to form a coating layer, thus obtaining a coated diaphragm.

[0018] Furthermore, in step S1, the pre-emulsion comprises the following components: by mass percentage, 10-12 wt% acrylic monomers, 1-2 wt% emulsifier, and the balance being deionized water; The concentration of the polyvinyl alcohol solution is 1-5%; The concentration of the initiator solution is 0.1-1%; The polyvinyl alcohol modified acrylic emulsion comprises the following components by mass percentage: 4-5 wt% acrylic monomers, 0.8-1.0 wt% emulsifier, 2-3 wt% polyvinyl alcohol, 0.2-0.3 wt% initiator, and the balance being deionized water.

[0019] Furthermore, the solid content of the polyvinyl alcohol modified acrylic emulsion concentrate is controlled at 5-10%.

[0020] Furthermore, in step S2, the dispersion comprises the following components: 0.2-0.6 wt% dispersant, 10-20 wt% binder, and the balance being ultrapure water, by mass percentage.

[0021] Furthermore, in step S2, polyvinylidene fluoride is added in the form of powder, and the particle size of the polyvinylidene fluoride powder is 1-5µm. The stirring process is as follows: first stir at 20-40 r / min for 60-80 min, then disperse at 1000-2000 r / min for 30-40 min; The coating slurry comprises the following components by mass percentage: 0.2-0.6 wt% dispersant, 10-20 wt% binder, 10-20 wt% polyvinylidene fluoride, 5-10 wt% polyvinyl alcohol modified acrylic emulsion, and the balance being ultrapure water.

[0022] Furthermore, in step S3, the thickness of the coating layer is 1-5 µm, and the areal density of the coating layer is 0.2-1.0 g / m³. 2 The coating speed is 10-150 m / min.

[0023] Furthermore, the base film undergoes surface modification, and the surface modification process is as follows: (1) Base film pretreatment: Plasma treatment of the base film; (2) Preparation of composite coating slurry: Modified montmorillonite and α-alumina were added to ultrapure water and stirred to disperse, thus obtaining an inorganic filler dispersion; polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), graphene nanosheets and silane coupling agent were added to the inorganic filler dispersion in sequence and stirred to obtain a composite coating slurry; (3) Coating and drying: The composite coating slurry is coated onto the base film using the doctor blade coating method. It is pre-dried at 80-100℃ for 8-10 min and then cross-linked and cured at 120-130℃ for 12-15 min to form a composite coating and obtain a modified base film.

[0024] Furthermore, the plasma treatment process is as follows: the gas selected is an argon / tetrafluoroethylene mixed gas with a volume ratio of (3-4):1, and fluorine-containing groups are introduced on the surface of the base film; the radio frequency power is 50-100W, the treatment time is 10-60s, and the working gas pressure is 10-100Pa.

[0025] Furthermore, the composite coating slurry comprises the following components by weight: 47.5-55 parts modified montmorillonite, 5-8 parts α-alumina, 38.5-42 parts PVDF-HFP, 1-1.5 parts graphene nanosheets, 0.5-1 parts silane coupling agent, and 80-100 parts ultrapure water.

[0026] Furthermore, the α-alumina particle size is 0.1-5µm; The particle size of PVDF-HFP is 1-10µm; The graphene nanosheets have a thickness of 4-20 nm and a particle size of 5-10 µm.

[0027] Furthermore, the stirring and dispersing process is as follows: first, stir at a speed of 200-400 r / min for 30-45 min, and then disperse at a speed of 1500-2000 r / min for 60-80 min.

[0028] Furthermore, the process conditions for blade coating are as follows: blade gap is 30-50µm, coating speed is 10-150m / min, and composite coating thickness is 2-3µm.

[0029] Furthermore, modified montmorillonite is obtained by the following process: Montmorillonite was added to a 5-7% hydrochloric acid solution and stirred at 60-70℃ for 18-24 hours to remove interlayer metal ions. After washing with deionized water until neutral (pH 6-7), it was dried at 110-120℃ for 8-12 hours. The dried montmorillonite was then added to an ethanol / water mixture, a silane coupling agent was added, and the mixture was stirred at 70-80℃ for 2-3 hours. After filtration and drying, modified montmorillonite was obtained.

[0030] Furthermore, the mass ratio of hydrochloric acid solution to montmorillonite is (3-4):1; The mass ratio of montmorillonite to the ethanol / water mixed solution is 1:(5-8); Ethanol / water mixed solution: The volume ratio of ethanol to water is (3-4):1; Montmorillonite has a particle size of 1-10µm.

[0031] Furthermore, the silane coupling agent is one or a mixture of KH-550, KH-551, A-151, and A171; the addition amount is 1.5-2 wt% of montmorillonite. Compared with the prior art, the beneficial effects of the present invention are: 1. In the polyvinyl alcohol modified acrylic emulsion of the present invention, both polyvinyl alcohol and acrylic acid have good adhesion. The coated diaphragm prepared by the adhesive has high adhesion performance to the electrode, thereby ensuring that a good adhesion effect between the coated diaphragm and the electrode can be achieved by cold pressing process.

[0032] 2. The synergistic effect of polyvinyl alcohol modified acrylic emulsion and polyacrylonitrile adhesive in the coating layer of this invention enables the coated separator to achieve high peel strength to the electrode through cold pressing without the need for hot pressing or heating. The preparation process omits the hot pressing step, reduces production steps and time, and improves production efficiency. This advantage is particularly obvious for the production of large batteries or thick cells, which can effectively shorten the production cycle and reduce production costs.

[0033] 3. The polyvinyl alcohol modified acrylic emulsion in the coating layer of this invention enhances the interfacial bonding: Through the emulsion polymerization process of pre-emulsion preparation, polyvinyl alcohol solution dissolution and gradient drop addition of initiator solution, polyvinyl alcohol and acrylic monomers form an interpenetrating network structure, which improves the interfacial adhesion between the coating layer and the base film, thereby improving the puncture resistance of the coated separator. This helps to prevent the coated separator from cracking or being damaged during battery assembly and use, and improves the safety and reliability of the battery.

[0034] 4. This invention modifies the surface of the base film and treats it with plasma: introducing fluorine-containing groups on the surface of the base film to enhance the chemical bonding force between the base film and the coating layer and reduce the thermal shrinkage rate; and applying a composite coating to the base film: forming a composite structure of modified montmorillonite rigid support and PVDF-HFP flexible network, thereby improving the mechanical strength and thermal stability of the base film.

[0035] In summary, the lithium-ion battery separator prepared by this invention has excellent adhesion and puncture strength, while also reducing battery-side energy consumption and improving production efficiency. It is suitable for cold pressing processes and solves the problems of low efficiency and high energy consumption in traditional hot pressing processes. Detailed Implementation

[0036] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0037] In the following specific implementation: All numbers of parts mentioned below refer to parts by weight, unless otherwise specified.

[0038] Base membrane: polyolefin separator, 12µm thick; The adhesive used is a polyacrylonitrile water-based adhesive, model LA133; The dispersant used is erucamide, model ER-CH; Polyvinylidene fluoride powder: PVDF-HFP, grafting rate of 6%, molecular weight of 800,000, average particle size of 3µm; Montmorillonite: average particle size is 2µm; α-Alumina: average particle size is 1µm; Graphene nanosheets: average thickness 10 nm, average particle size 5 µm.

[0039] Example 1: A method for preparing a cold-pressed lithium-ion battery separator, comprising the following steps: S1: Preparation of polyvinyl alcohol modified acrylic emulsion: S1-1: Mix 10g acrylic acid, 2g sodium dodecyl sulfate and 88g deionized water, stir at 300r / min for 30min to pre-emulsify, and prepare a pre-emulsion. S1-2: Add 5g of polyvinyl alcohol to 95g of deionized water, heat to 90℃ and stir to dissolve. After complete dissolution, cool to room temperature to obtain a polyvinyl alcohol solution. S1-3: Add 0.5g of potassium persulfate to 29.5g of deionized water and stir at 300r / min for 30min to obtain an initiator solution; S1-4: The polyvinyl alcohol solution was heated to 80℃, and the pre-emulsion and initiator solution were added dropwise. The mixture was stirred at 500 r / min and kept at this temperature for 2 h. After cooling to room temperature, a polyvinyl alcohol-modified acrylic emulsion was obtained. The solid content of the polyvinyl alcohol-modified acrylic emulsion was 10%. S2: Preparation of coating slurry: S2-1: Mix the dispersant, binder and ultrapure water, and stir at 30 r / min for 10 min to prepare a dispersion. S2-2: Add polyvinylidene fluoride, stir at 30 r / min for 60 min, then stir at 1000 r / min for 30 min, add polyvinyl alcohol modified acrylic emulsion, stir at 30 r / min for 20 min to obtain coating slurry; The coating slurry comprises the following components by mass percentage: 0.2 wt% dispersant erucamide, 10 wt% polyacrylonitrile waterborne adhesive, 15 wt% polyvinylidene fluoride, 5 wt% polyvinyl alcohol modified acrylic emulsion, and the balance being ultrapure water. S3: Preparation of coated diaphragm: The coating slurry was roller-coated onto the surface of a base film with a thickness of 12µm and dried at 65℃ to form a coating layer, thus obtaining a coated diaphragm. The coating thickness is 2µm, and the areal density of the coating is 1.0g / m³. 2 The coating speed is 100 m / min.

[0040] Example 2: A method for preparing a cold-pressed lithium-ion battery separator, comprising the following steps: S1: Preparation of polyvinyl alcohol modified acrylic emulsion: S1-1: Mix 10g acrylic acid, 2g sodium dodecyl sulfate and 88g deionized water, stir at 300r / min for 30min to pre-emulsify, and prepare a pre-emulsion. S1-2: Add 5g of polyvinyl alcohol to 95g of deionized water, heat to 90℃ and stir to dissolve. After complete dissolution, cool to room temperature to obtain a polyvinyl alcohol solution. S1-3: Add 0.5g of potassium persulfate to 29.5g of deionized water and stir at 300r / min for 30min to obtain an initiator solution; S1-4: The polyvinyl alcohol solution was heated to 80℃, and the pre-emulsion and initiator solution were added dropwise. The mixture was stirred at 500 r / min and kept at this temperature for 2 h. After cooling to room temperature, a polyvinyl alcohol-modified acrylic emulsion was obtained. The solid content of the polyvinyl alcohol-modified acrylic emulsion was 10%. S2: Preparation of coating slurry: S2-1: Mix the dispersant, binder and ultrapure water, and stir at 30 r / min for 10 min to prepare a dispersion. S2-2: Add polyvinylidene fluoride, stir at 30 r / min for 60 min, then stir at 1000 r / min for 30 min, add polyvinyl alcohol modified acrylic emulsion, stir at 30 r / min for 20 min to obtain coating slurry; The coating slurry comprises the following components by mass percentage: 0.2 wt% dispersant erucamide, 10 wt% polyacrylonitrile waterborne adhesive, 15 wt% polyvinylidene fluoride, 8 wt% polyvinyl alcohol modified acrylic emulsion, and the balance being ultrapure water. S3: Preparation of coated diaphragm: The coating slurry was roller-coated onto the surface of a base film with a thickness of 12µm and dried at 65℃ to form a coating layer, thus obtaining a coated diaphragm. The coating thickness is 2µm, and the areal density of the coating is 1.0g / m³. 2 The coating speed is 100 m / min.

[0041] Example 3: A method for preparing a cold-pressed lithium-ion battery separator, comprising the following steps: S1-1: Mix 10g acrylic acid, 2g sodium dodecyl sulfate and 88g deionized water, stir at 300r / min for 30min to pre-emulsify, and prepare a pre-emulsion. S1-2: Add 5g of polyvinyl alcohol to 95g of deionized water, heat to 90℃ and stir to dissolve. After complete dissolution, cool to room temperature to obtain a polyvinyl alcohol solution. S1-3: Add 0.5g of potassium persulfate to 29.5g of deionized water and stir at 300r / min for 30min to obtain an initiator solution; S1-4: The polyvinyl alcohol solution was heated to 80℃, and the pre-emulsion and initiator solution were added dropwise. The mixture was stirred at 500 r / min and kept at this temperature for 2 h. After cooling to room temperature, a polyvinyl alcohol-modified acrylic emulsion was obtained. The solid content of the polyvinyl alcohol-modified acrylic emulsion was 10%. S2: Preparation of coating slurry: S2-1: Mix the dispersant, binder and ultrapure water, and stir at 30 r / min for 10 min to prepare a dispersion. S2-2: Add polyvinylidene fluoride, stir at 30 r / min for 60 min, then stir at 1000 r / min for 30 min, add polyvinyl alcohol modified acrylic emulsion, stir at 30 r / min for 20 min to obtain coating slurry; The coating slurry comprises the following components by mass percentage: 0.2 wt% dispersant erucamide, 10 wt% polyacrylonitrile waterborne adhesive, 15 wt% polyvinylidene fluoride, 10 wt% polyvinyl alcohol modified acrylic emulsion, and the balance being ultrapure water. S3: Preparation of coated diaphragm: The coating slurry was roller-coated onto the surface of a base film with a thickness of 12µm and dried at 65℃ to form a coating layer, thus obtaining a coated diaphragm. The coating thickness is 2µm, and the areal density of the coating is 1.0g / m³. 2 The coating speed is 100 m / min.

[0042] Example 4: A method for preparing a cold-pressed lithium-ion battery separator, comprising the following steps: S1: Preparation of polyvinyl alcohol modified acrylic emulsion: S1-1: Mix 10g acrylic acid, 2g sodium dodecyl sulfate and 88g deionized water, stir at 300r / min for 30min to pre-emulsify, and prepare a pre-emulsion. S1-2: Add 5g of polyvinyl alcohol to 95g of deionized water, heat to 90℃ and stir to dissolve. After complete dissolution, cool to room temperature to obtain a polyvinyl alcohol solution. S1-3: Add 0.5g of potassium persulfate to 29.5g of deionized water and stir at 300r / min for 30min to obtain an initiator solution; S1-4: The polyvinyl alcohol solution was heated to 80℃, and the pre-emulsion and initiator solution were added dropwise. The mixture was stirred at 500 r / min and kept at this temperature for 2 h. After cooling to room temperature, a polyvinyl alcohol-modified acrylic emulsion was obtained. The solid content of the polyvinyl alcohol-modified acrylic emulsion was 10%. S2: Preparation of coating slurry: S2-1: Mix the dispersant, binder and ultrapure water, and stir at 30 r / min for 10 min to prepare a dispersion. S2-2: Add polyvinylidene fluoride, stir at 30 r / min for 60 min, then stir at 1000 r / min for 30 min, add polyvinyl alcohol modified acrylic emulsion, stir at 30 r / min for 20 min to obtain coating slurry; The coating slurry comprises the following components by mass percentage: 0.2 wt% dispersant erucamide, 10 wt% polyacrylonitrile waterborne adhesive, 15 wt% polyvinylidene fluoride, 5 wt% polyvinyl alcohol modified acrylic emulsion, and the balance being ultrapure water. S3: Preparation of coated diaphragm: The coating slurry was roller-coated onto the surface of a modified base film with a thickness of 14µm and dried at 65℃ to form a coating layer, thus obtaining a coated diaphragm. The coating thickness is 2µm, and the areal density of the coating is 1.0g / m³. 2 The coating speed is 100 m / min.

[0043] The modified base film is prepared by the following process: (1) Base film pretreatment: plasma treatment of the base film; the plasma treatment process is as follows: argon / tetrafluoroethylene mixed gas is selected with a volume ratio of 3:1; radio frequency power is 80W, treatment time is 25s, and working pressure is 50Pa. (2) Preparation of composite coating slurry: Modified montmorillonite and α-alumina were added to ultrapure water, stirred at 300 r / min for 40 min, and then dispersed at 2000 r / min for 60 min to obtain inorganic filler dispersion; PVDF-HFP, graphene nanosheets and silane coupling agent KH-550 were added to inorganic filler dispersion in sequence and stirred until uniformly mixed to obtain composite coating slurry; The composite coating slurry comprises the following components by weight: 50 parts modified montmorillonite, 8 parts α-alumina, 40 parts PVDF-HFP, 1 part graphene nanosheets, 1 part silane coupling agent, and 80 parts ultrapure water. (3) Coating and drying: The composite coating slurry is coated onto the base film using a doctor blade coating method, pre-drying at 80℃ for 8 min, and cross-linking and curing at 120℃ for 12 min to form a composite coating and obtain a modified base film. The process conditions for blade coating are: blade gap of 50µm, coating speed of 50m / min, and composite coating thickness of 2µm.

[0044] Modified montmorillonite is obtained by the following process: Montmorillonite was added to a 5% hydrochloric acid solution at a mass ratio of 3:1. The mixture was stirred at 60°C for 24 hours to remove interlayer metal ions. After washing with deionized water until neutral (pH 7), the mixture was dried at 110°C for 12 hours. The dried montmorillonite was then added to an ethanol / water mixture (volume ratio of 3:1) at a ratio of 1:7. 2 wt% of silane coupling agent KH-551 was added to the mixture. The mixture was stirred at 80°C for 2 hours. After filtration and drying, modified montmorillonite was obtained.

[0045] Example 5: A method for preparing a cold-pressed lithium-ion battery separator, comprising the following steps: S1: Preparation of polyvinyl alcohol modified acrylic emulsion: S1-1: Mix 10g acrylic acid, 2g sodium dodecyl sulfate and 88g deionized water, stir at 300r / min for 30min to pre-emulsify, and prepare a pre-emulsion. S1-2: Add 5g of polyvinyl alcohol to 95g of deionized water, heat to 90℃ and stir to dissolve. After complete dissolution, cool to room temperature to obtain a polyvinyl alcohol solution. S1-3: Add 0.5g of potassium persulfate to 29.5g of deionized water and stir at 300r / min for 30min to obtain an initiator solution; S1-4: The polyvinyl alcohol solution was heated to 80℃, and the pre-emulsion and initiator solution were added dropwise. The mixture was stirred at 500 r / min and kept at this temperature for 2 h. After cooling to room temperature, a polyvinyl alcohol-modified acrylic emulsion was obtained. The solid content of the polyvinyl alcohol-modified acrylic emulsion was 10%. S2: Preparation of coating slurry: S2-1: Mix the dispersant, binder and ultrapure water, and stir at 30 r / min for 10 min to prepare a dispersion. S2-2: Add polyvinylidene fluoride, stir at 30 r / min for 60 min, then stir at 1000 r / min for 30 min, add polyvinyl alcohol modified acrylic emulsion, stir at 30 r / min for 20 min to obtain coating slurry; The coating slurry comprises the following components by mass percentage: 0.2 wt% dispersant erucamide, 10 wt% polyacrylonitrile waterborne adhesive, 15 wt% polyvinylidene fluoride, 5 wt% polyvinyl alcohol modified acrylic emulsion, and the balance being ultrapure water. S3: Preparation of coated diaphragm: The coating slurry was roller-coated onto the surface of a modified base film with a thickness of 15µm and dried at 65℃ to form a coating layer, thus obtaining a coated diaphragm. The coating thickness is 2µm, and the areal density of the coating is 1.0g / m³. 2 The coating speed is 100 m / min.

[0046] The modified base film is prepared by the following process: (1) Base film pretreatment: plasma treatment of the base film; the plasma treatment process is as follows: the gas selection is argon / tetrafluoroethylene mixed gas with a volume ratio of 4:1; the radio frequency power is 100W, the treatment time is 10s, and the working gas pressure is 10Pa. (2) Preparation of composite coating slurry: Modified montmorillonite and α-alumina were added to ultrapure water, stirred at 400 r / min for 30 min, and then dispersed at 1500 r / min for 80 min to obtain inorganic filler dispersion; PVDF-HFP, graphene nanosheets and silane coupling agent KH-550 were added to inorganic filler dispersion in sequence and stirred until uniformly mixed to obtain composite coating slurry; The composite coating slurry comprises the following components by weight: 53 parts modified montmorillonite, 5 parts α-alumina, 40 parts PVDF-HFP, 1 part graphene nanosheets, 1 part silane coupling agent, and 100 parts ultrapure water. (3) Coating and drying: The composite coating slurry is coated onto the base film using a doctor blade coating method, pre-drying at 100℃ for 10 min and cross-linking and curing at 130℃ for 15 min to form a composite coating and obtain a modified base film. The process conditions for blade coating are: blade gap of 30µm, coating speed of 100m / min, and composite coating thickness of 3µm.

[0047] Modified montmorillonite is obtained by the following process: Montmorillonite was added to a 6% hydrochloric acid solution at a mass ratio of 4:1. The mixture was stirred at 70°C for 18 hours to remove interlayer metal ions. After washing with deionized water until neutral (pH 6), the mixture was dried at 120°C for 8 hours. The dried montmorillonite was then added to an ethanol / water mixture (volume ratio 4:1) at a ratio of 1:5. 1.5 wt% of silane coupling agent KH-551 was added to the mixture. The mixture was stirred at 70°C for 3 hours. After filtration and drying, modified montmorillonite was obtained.

[0048] Comparative Example 1: Based on Example 1, the preparation of the coating slurry was adjusted without the addition of polyvinyl alcohol-modified acrylic emulsion, including the following steps: S1: Preparation of coating slurry: S1-1: Mix the dispersant, binder and ultrapure water, and stir at 30 r / min for 10 min to prepare a dispersion. S1-2: Add polyvinylidene fluoride, stir at 30 r / min for 60 min, then stir at 1000 r / min for 30 min to obtain the coating slurry; The coating slurry comprises the following components by mass percentage: 0.2 wt% dispersant erucamide, 10 wt% polyacrylonitrile waterborne adhesive, 15 wt% polyvinylidene fluoride, and the balance being ultrapure water; S3: Preparation of coated diaphragm: The coating slurry was roller-coated onto the surface of a base film with a thickness of 12µm and dried at 65℃ to form a coating layer, thus obtaining a coated diaphragm. The coating thickness is 2µm, and the areal density of the coating is 1.0g / m³. 2 The coating speed is 100 m / min.

[0049] Comparative Example 2: A polyolefin membrane was used without any coating.

[0050] Comparative Example 3: Based on Example 4, the modified montmorillonite in the composite coating slurry was changed to montmorillonite. The only difference from Example 4 is that the composite coating slurry includes the following components by mass: 50 parts montmorillonite, 8 parts α-alumina, 40 parts PVDF-HFP, 1 part graphene nanosheets, 1 part silane coupling agent, and 80 parts ultrapure water.

[0051] Comparative Example 4: The only difference from Example 4 is that the modified base film was not subjected to plasma treatment.

[0052] Experiment: The membranes prepared in Examples 1-5 and Comparative Examples 1-4 were used to prepare samples, and their performance was tested. The test results are shown in Table 1. Positive electrode-cold press peel strength: The separator and the positive electrode sheet are bonded together by cold pressing to make a test sample. The separator is peeled from the positive electrode sheet at a speed of 50 mm / min using the 180° peel method. The force value during the peeling process is recorded and the average value is taken as the peel strength. Air permeability: The time required for 100 mL of air to pass through a 100 cm² membrane was measured using a TAPPI T460 Gurley air permeability tester. The air permeability reflects the porosity and pore size distribution of the membrane. The shorter the time, the better the air permeability. Puncture strength: Using an electronic universal testing machine, the diaphragm was fixed on a circular clamp, and a puncture needle with a hemispherical tip (1 mm in diameter) was used to puncture the diaphragm vertically at 100 mm / min. The maximum force value during the puncture was recorded. Heat shrinkage: Cut a 100mm×100mm diaphragm sample, place it in a heat shrinkage test chamber, heat it at 105℃ for 1 hour, and then measure the dimensional change rate of the sample in the longitudinal (MD) and transverse (TD) directions. The calculation formula is: heat shrinkage (%) = (initial size - shrinkage size) / initial size.

[0053]

[0054] Conclusion: The data comparison in the table shows that the performance of the separators prepared in Comparative Examples 1-4 is significantly worse than that of the separators prepared in Examples 1-5. Comparative Example 1, based on Example 1, did not add polyvinyl alcohol-modified acrylic emulsion to the coating slurry. The separator prepared in Comparative Example 1 showed significantly worse positive electrode-cold-press peel strength, heat shrinkage, and puncture strength compared to the separators prepared in the examples, while its air permeability was improved. This indicates that polyvinyl alcohol-modified acrylic emulsion can enhance interfacial bonding and improve the mechanical strength of the separator. Comparative Example 2 used a polyolefin-based membrane as the battery separator without a coating. Compared to the separators prepared in the examples, its positive electrode-cold-press peel strength, heat shrinkage, and puncture strength were significantly worse. The performance of the modified montmorillonite in the composite coating slurry was significantly worse than that of the diaphragm prepared in the example, while the air permeability was improved. Comparative Example 3 was based on Example 4, but the modified montmorillonite in the composite coating slurry was replaced with montmorillonite. Compared with the diaphragm prepared in the example, its positive electrode-cold pressure peel strength, heat shrinkage, and puncture strength were significantly worse, while the air permeability was not significantly different. Comparative Example 4 was based on Example 4, but the modified base film was not subjected to plasma treatment. Compared with the diaphragm prepared in the example, its positive electrode-cold pressure peel strength, heat shrinkage, and puncture strength were significantly worse, while the air permeability was not significantly different.

[0055] Comparing Examples 1-3 and Comparative Examples 1-2, it can be seen that as the amount of polyvinyl alcohol modified acrylic emulsion added to the coating slurry gradually increases: The positive electrode-cold pressing peel performance of the corresponding coated separator is getting better and better, that is, the adhesion to the positive electrode sheet is getting better and better (under the same PVDF coating layer density), and all of them are higher than the coated separator corresponding to the coating slurry without the addition of polyvinyl alcohol modified acrylic emulsion. The corresponding heat shrinkage and puncture performance of the coated diaphragm are increasingly better (under the same coating layer adhesive layer density), and are both superior to the coated diaphragm corresponding to the coating layer slurry without the addition of polyvinyl alcohol modified acrylic emulsion, which confirms the effectiveness of polyvinyl alcohol modified acrylic emulsion in improving the safety performance of the diaphragm. The air permeability of the coated diaphragm deteriorates (under the same coating layer adhesive layer density), and is worse than that of the coated diaphragm corresponding to the coating slurry without the addition of polyvinyl alcohol modified acrylic emulsion. Therefore, in order to balance the various performance aspects of the coated diaphragm, the amount of polyvinyl alcohol modified acrylic emulsion added should be moderate, and more is not necessarily better. Compared with existing water-based polyvinylidene fluoride coating technology, the coated diaphragm prepared by this invention also has high electrode bonding performance and high safety under cold pressing conditions, and has good application prospects in the field of diaphragms.

[0056] Comparing Examples 4-5 and Comparative Examples 3-4, it can be seen that plasma treatment can enhance the chemical bonding force between the base film and the coating layer and reduce the thermal shrinkage rate; compared with montmorillonite, modified montmorillonite can better combine with other components and enhance the mechanical strength and thermal stability of the base film.

[0057] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A lithium-ion battery separator suitable for cold pressing, characterized in that: It includes the following structure: a base film and a coating layer disposed on the surface of the base film; The coating layer comprises the following components: polyvinylidene fluoride, adhesive, dispersant, polyvinyl alcohol, acrylic monomers, emulsifier, and initiator; The coating layer is obtained by applying a coating slurry, which includes the following components by mass percentage: 0.2-0.6 wt% dispersant, 10-20 wt% binder, 10-20 wt% polyvinylidene fluoride, 5-10 wt% polyvinyl alcohol modified acrylic emulsion, and the balance being ultrapure water. The polyvinyl alcohol modified acrylic emulsion is prepared by the following process: Acrylic monomers, emulsifiers, and deionized water are mixed to prepare a pre-emulsion; a polyvinyl alcohol solution is heated to 70-80℃, and the pre-emulsion and initiator solution are added dropwise, and the reaction is maintained at this temperature to obtain a polyvinyl alcohol modified acrylic emulsion.

2. The lithium-ion battery separator suitable for cold pressing according to claim 1, characterized in that: The acrylic monomer is one or more of acrylic acid, methyl acrylate, ethyl acrylate, and methyl methacrylate.

3. The lithium-ion battery separator suitable for cold pressing according to claim 1, characterized in that: The base membrane is a polyolefin separator; The adhesive is a polyacrylonitrile polymer, and the dispersant is an aliphatic amide dispersant.

4. A lithium-ion battery separator suitable for cold pressing according to claim 1, characterized in that: The emulsifier is one or a mixture of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, fatty alcohol polyoxyethylene ether, and sodium allyl hydroxypropyl sulfonate.

5. A lithium-ion battery separator suitable for cold pressing according to claim 1, characterized in that: The initiator is one or a mixture of ammonium persulfate, potassium persulfate, and sodium persulfate.

6. A method for preparing a lithium-ion battery separator suitable for cold pressing, characterized in that: Includes the following steps: S1: Preparation of polyvinyl alcohol modified acrylic emulsion: Acrylic monomers, emulsifiers, and deionized water are mixed to prepare a pre-emulsion; a polyvinyl alcohol solution is heated to 70-80℃, and the pre-emulsion and initiator solution are added dropwise, and the reaction is maintained at the temperature to obtain a polyvinyl alcohol modified acrylic emulsion. S2: Preparation of coating slurry: Dispersant, binder and ultrapure water are stirred to form a dispersion; polyvinylidene fluoride and polyvinyl alcohol modified acrylic emulsion are added in sequence and stirred to obtain coating slurry; S3: Preparation of coated diaphragm: The coating slurry is applied to the surface of the base film and dried to form a coating layer, thus obtaining a coated diaphragm. The components for preparing the polyvinyl alcohol modified acrylic emulsion include, by mass percentage: 4-5 wt% acrylic monomers, 0.8-1.0 wt% emulsifier, 2-3 wt% polyvinyl alcohol, 0.2-0.3 wt% initiator, and the balance being deionized water.

7. The method for preparing a cold-pressed lithium-ion battery separator according to claim 6, characterized in that: The pre-emulsion comprises the following components: 10-12 wt% acrylic monomers, 1-2 wt% emulsifier, and the balance being deionized water, by mass percentage.

8. The method for preparing a cold-pressed lithium-ion battery separator according to claim 6, characterized in that: The coating layer has a thickness of 1-5 µm and a surface density of 0.2-1.0 g / m³. 2 The coating speed is 10-150 m / min.

9. The method for preparing a cold-pressed lithium-ion battery separator according to claim 6, characterized in that: The base film undergoes surface modification, and the surface modification process is as follows: (1) Base film pretreatment: Plasma treatment of the base film; (2) Preparation of composite coating slurry: Modified montmorillonite and α-alumina were added to ultrapure water and stirred to disperse, thus obtaining an inorganic filler dispersion; polyvinylidene fluoride-hexafluoropropylene copolymer, graphene nanosheets and silane coupling agent were added to the inorganic filler dispersion in sequence and stirred to obtain a composite coating slurry; (3) Coating and drying: The composite coating slurry is coated onto the base film using a doctor blade coating method and then dried to form a composite coating, thus obtaining a modified base film; The modified montmorillonite is prepared by the following process: montmorillonite is added to a 5-7% hydrochloric acid solution and stirred at 60-70℃ for 18-24 hours to remove interlayer metal ions. After washing with deionized water until neutral, it is dried at 110-120℃ for 8-12 hours. The dried montmorillonite is added to an ethanol / water mixed solution, a silane coupling agent is added, and the mixture is stirred at 70-80℃ for 2-3 hours. After filtration and drying, the modified montmorillonite is obtained.

Citation Information

Patent Citations

  • Normal-temperature cold-pressed adhesive coating diaphragm and preparation method thereof

    CN117060008A